Academic Senate Minutes 2006-09-28 - Academic Senate:::::::::
Report of the Chair. Approval of Agenda. Minutes delayed. End of Year report from APC. Update on WASC. Special Report: Bonnie Sugiyama, Director of the Center for Gender, Cultures and Sexualities. Special Report from FSAC. Special Report from APC. Animal Care Policy Approved. Associated Students Report. President Report. Chair-Elect Report. Statewide Senators Report.